Digital Leadership in Improving Organizational Employee Performance - Rumapea, Elsa Oktavera; Aprinawati, Aprinawati; Siboro, Indah Putri; Manurung, Karina; Khairunnisa, Khairunnisa; Silitonga, Theresia Putri; Ovianti, Widya (Holistic Science, 2024)
Digital leadership has become a strategic element in supporting employee performance amidst the rapid development of technology and digital transformation. This study aims to analyze in depth how digital leadership affects employee performance, with a focus on technology adaptation, innovation, and renewal of organizational work culture. The research method uses a qualitative approach based on literature review, which includes analysis of journal articles, books, and relevant online publications. The results of the study indicate that effective digital leaders are not only able to utilize technology strategically, but also create a work environment that supports flexibility, collaboration, and innovation. In addition, digital leaders play an important role in strengthening employee commitment through technology-based empowerment and motivation. These findings confirm that digital leadership can improve operational efficiency, encourage creativity in problem solving, and create sustainable added value for the organization. This study is expected to provide theoretical and practical contributions in the development of digital leadership models in various sectors, especially in facing the challenges of the digital transformation era.